2022
DOI: 10.1186/s12935-021-02410-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of porcine ALG and rabbit ATG on outcomes of HLA-haploidentical hematopoietic stem cell transplantation for patients with acquired aplastic anemia

Abstract: Objective To evaluate the efficacy and safety of P-ALG (porcine anti-lymphocyte globulin) and R-ATG (rabbit anti-thymocyte globulin) in the conditioning regime for patients with acquired aplastic anemia who underwent HLA-haploidentical hematopoietic stem cell transplantation (halpo-HSCT). Methods A total of 91 patients with acquired aplastic anemia who received haplo-HSCT at our center between January 2014 and December 2020 were retrospectively rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Three patients in the p‐ALG 90 mg/kg group and four patients in the r‐ATG group failed to receive neutrophil engraftment due to primary graft failures and subsequently died due to infections. The previous study indicated that patients in the p‐ALG group had a lower incidence of CMV viraemia than the r‐ATG group after halpo‐HSCT 25 . In our study, patients in the group receiving a higher dose of p‐ALG (90 mg/kg) had the highest rates of infection.…”
Section: Discussionsupporting
confidence: 45%
See 2 more Smart Citations
“…Three patients in the p‐ALG 90 mg/kg group and four patients in the r‐ATG group failed to receive neutrophil engraftment due to primary graft failures and subsequently died due to infections. The previous study indicated that patients in the p‐ALG group had a lower incidence of CMV viraemia than the r‐ATG group after halpo‐HSCT 25 . In our study, patients in the group receiving a higher dose of p‐ALG (90 mg/kg) had the highest rates of infection.…”
Section: Discussionsupporting
confidence: 45%
“…The previous study indicated that patients in the p-ALG group had a lower incidence of CMV viraemia than the r-ATG group after halpo-HSCT. 25 In our study, patients in the group receiving a higher dose of p-ALG (90 mg/kg) had the highest rates of infection. In addition, the incidence of CMV reactivation in the p-ALG 75 mg/kg group was significantly lower than that in the r-ATG group (p = 0.046).…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Graft versus host disease (GVHD) prophylaxis and supportive care were as described previously ( 19 ).…”
Section: Methodsmentioning
confidence: 99%
“…The Mount Sinai Acute GVHD International Consortium criteria were used to diagnose and grade acute GVHD (aGVHD) ( 20 ). Cytomegalovirus (CMV) and Epstein–Barr virus (EBV) viremia was defined as before ( 19 ). Severe bacterial infection referred to bacteremia or severe tissue infections.…”
Section: Methodsmentioning
confidence: 99%